Experiences of supported isolation in returning travellers during the early COVID-19 response: a qualitative interview study - Neil Greenberg; Isabel Oliver; Richard Amlot; Dale Weston; Simon Wessely; G James Rubin; Holly Carter; Charlotte Robin; Louis Gauntlett (BMJ Open)
Objectives (1) To understand the experiences and perceptions of those who underwent supported isolation, particularly in relation to factors that were associated with improved compliance and well-being; (2) to inform recommendations for the management of similar supported isolation procedures.Design We carried out a qualitative study using semistructured interviews to capture participants’ experiences and perceptions of supported isolation. Data were analysed using the framework approach, a type of thematic analysis that is commonly used in research that has implications for policy.Setting Telephone interviews carried out within approximately 1 month of an individual leaving supported isolation.Participants 26 people who underwent supported isolation at either Arrowe Park Hospital (n=18) or Kents Hill Park Conference Centre (n=8) after being repatriated from Wuhan in January to February 2020.Results Six key themes were identified: factors affecting compliance with supported isolation; risk perceptions around catching COVID-19; management of supported isolation; communication with those outside supported isolation; relationship with others in supported isolation; and feelings on leaving supported isolation. Participants were willing to undergo supported isolation because they understood that it would protect themselves and others. Positive treatment by staff was fundamental to participants’ willingness to comply with isolation procedures. Despite the high level of compliance, participants expressed some uncertainty about what the process would involve.Conclusions As hotel quarantine is introduced across the UK for international arrivals, our findings suggest that those in charge should: communicate effectively before, during and after quarantine, emphasising why quarantine is important and how it will protect others; avoid coercion if possible and focus on supporting and promoting voluntary compliance; facilitate shared social experiences for those in quarantine; and ensure all necessary supplies are provided. Doing so is likely to increase adherence and reduce any negative effects on well-being.